2014
DOI: 10.3109/13651501.2014.981545
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of post-traumatic stress disorder in patients with burn injuries, and their quality of life

Abstract: PTSD seems to be an important health issue in patients with burn injuries. Clinicians who attempt to tailor treatment interventions should keep in mind that these patients require psychosocial rehabilitation, as well as physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…We know that physical and mental health are interrelated [10] and that physical injuries and material losses are also strongly associated with PTSD [13, 14]. Long-term financial problems are one of the many important factors affecting quality of life (QoL) [8, 12, 20, 21]. Health-related quality of life (HRQoL) includes both physical and mental dimensions [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that physical and mental health are interrelated [10] and that physical injuries and material losses are also strongly associated with PTSD [13, 14]. Long-term financial problems are one of the many important factors affecting quality of life (QoL) [8, 12, 20, 21]. Health-related quality of life (HRQoL) includes both physical and mental dimensions [22].…”
Section: Introductionmentioning
confidence: 99%
“…A composite measure of physical and psychological health is HRQoL, as assessed, for example, by short form-12 or − 36 [23]. Experiencing long-term financial problems is one of several important factors affecting quality of life [10, 12, 20, 21]. Through this continuous cycle, trauma may become a personal problem that evolves into a family problem.…”
Section: Introductionmentioning
confidence: 99%
“…Scores on mental health and emotional functioning in burn survivors are below the national average up to three years after injury [9]. A diagnosis of Posttraumatic Stress Disorder (PTSD) is a risk factor for poor functional outcomes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Burns can produce negative emotions such as anxiety and depression, which in turn affect the quality of life (Kowal-Vern and Criswell, 2005; Miller et al, 2013; Cakir et al, 2015; Spronk et al, 2018a). Studies have shown that the quality of life of patients with burn scars is moderate.…”
Section: Introductionmentioning
confidence: 99%